Discovery of False Elite Controllers: HIV Antibody-Positive RNA-Negative Blood Donors Found To Be on Antiretroviral Therapy. (5th April 2019) - Sykes, Wendy; Van den Berg, Karin; Jacobs, Genevieve; Jauregui, Adam; Roubinian, Nareg; Wiesner, Lubbe; Maartens, Gary; Swanevelder, Ronel; Custer, Brian; Busch, Michael; Jentsch, Ute; Murphy, Edward L; et al.
Abstract: Background: An increase in potential HIV elite controllers (EC) and anecdotal reports of antiretroviral therapy (ART) use among South African blood donors led us to verify EC status. Methods: Stored plasma samples from potential EC were tested for ART drugs. Demographic and temporal associations were examined using multivariable logistic regression. Results: Of 226 potential EC, 150 (66.4%) had detectable ART with increasing prevalence by year (OR = 7.57 for 2016 vs 2010, 95% confidence interval, 1.96–32.17). Discussion: False presumptive EC status due to undisclosed ART represents a growing proportion of potential EC donors in South Africa coincident with the country's ART rollout. Abstract : Of 226 South African blood donors presumed to be HIV elite controllers (EC), 66.4% tested positive for antiretroviral therapy (ART). The proportion of false presumptive EC and undisclosed ART increased over the study period, coincident with a national ART rollout.